Addressing Beijing Platform for Actions’ (BPfA) Area of Concerns Experienced by Women and Girls: Assessing the Indonesian, Kosovar, and German Repatriation Policies - Nuri Widiastuti Veronika (Universitas Islam Indonesia, 2021)
The demise of ISIS in 2017 brought about dilemmatic situations for some governments in dealing with the issues of foreign terrorist fighters (FTFs), especially women and children currently living at Northern Syrian camps. Women and children experience poverty, lacking access to education, minimal access to healthcare, violence against women, violation of women’s human rights, media stereotyping of women and girls’ vulnerabilities, which have been identified as parts of the 12 critical areas of concern addressed within the Beijing Platform for Action (BPfA), an international framework to protect the rights of women in armed conflicts. Employing Feminist Security Studies as the framework for analysis, this paper analyses how the areas of concern of BPfA experienced by women and girls in the camps have been responded by the government’s repatriation policies. This paper is a qualitative study by employing semi-structured interviews for the primary data collection complemented with relevant policy documents and secondary data from scholarly articles and media reporting. This paper discusses some areas of concern addressed in BPfA experienced by women in ex-ISIS camps and investigate countries responses to these concerns by looking at the Indonesian, Kosovar and German governments’ experience. The results of this study show that policies taken by most governments in dealing with repatriation issues have not considered the Beijing Platform for Actions’ strategic objectives resulting in further deprivation and human rights violation dealt by women and girls in the camps.